Alpski botanični vrt Juliana in seznami rastlin - Praprotnik, Nada (Scopolia, 2012)
The article presents a detailed description of the history of Juliana Alpine Botanical Garden in the Trenta Valley, Slovenia, mainly covering the period after World War II. Various documents and records, which have been neither known nor published, have survived from this particular time and illuminate, in detail, the events taking place in the Garden. The article enumerates Juliana's guidebooks and makes references to seed gathering, lists of plants (Index seminum), various signboards for the garden and nameplates for its plants. A list of plants that used to thrive in the Garden and still do is also given. The various lists have been written by Albert Bois de Chesne, Julius Kugy, Angela Piskernik, Ciril Jeglič, Tone Wraber, and Nada Praprotnik. The common list embraces no less than 1,343 taxa.
Keywords: botanika; Rhododendron-Park Bremen; botany; botanični vrtovi; botanical gardens; Juliana; history; zgodovina; rastlinstvo; systematics; plant taxa; rastlinski taxoni; Alpe; Alps; Slovenia; Slovenija